Native grasslands of the Great Plains of North America: using prairie grouse as flagship species for restoration - Yeats, Scott, speaker; Haufler, Jonathan, speaker; Mehl, Carolyn, speaker; Riley, Terry, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
The grasslands of the Great Plains of North America historically covered over 240 million hectares and supported a wide diversity of ecosystems and wildlife species. Today, many of these ecosystems are among those at greatest risk and many of the species they support are in serious decline. While some public lands exist, the Great Plains are predominantly in private ownership. This means that conservation efforts must first recognize what private landowners require from their lands, and then make conservation initiatives compatible with and workable within landowner requirements. Maintaining and restoring native grassland ecosystems is essential if maintaining the wildlife and biodiversity of the Great Plains is a goal. Prairie grouse (lesser and greater prairie-chickens and sharp-tailed grouse) are effective flagship species for emphasizing the need for grassland restoration and indicators of the sizes and distributions of needed grassland areas. Prairie Grouse Partners, a collaborative effort of the Ecosystem Management Research Institute, North American Grouse Partnership, Pheasants Forever, Theodore Roosevelt Conservation Partnership, American Bird Conservancy, and the Mule Deer Foundation, have launched an initiative to restore native grasslands using prairie grouse as flagship species. Initial projects have engaged willing landowners in the application of treatments to restore grasslands. Management practices including prescribed burning, prescribed grazing, seeding of native species, chemical control of invasive species, and mechanical control of invading woody species have been applied and monitored to determine their effectiveness across different types of grassland sites. Initial results are promising, but larger coordinated efforts are needed to meet this conservation challenge.
Moderator: Terry Riley.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
Video presenter: Jonathan Haufler.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses